2012
DOI: 10.1667/rr2819.1
|View full text |Cite
|
Sign up to set email alerts
|

Radiation and Smoking Effects on Lung Cancer Incidence by Histological Types Among Atomic Bomb Survivors

Abstract: While the risk of lung cancer associated separately with smoking and radiation exposure has been widely reported, it is not clear how smoking and radiation together contribute to the risk of specific lung cancer histological types. With individual smoking histories and radiation dose estimates, we characterized the joint effects of radiation and smoking on type-specific lung cancer rates among the Life Span Study cohort of Japanese atomic bomb survivors. Among 105,404 cohort subjects followed between 1958 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 34 publications
2
49
0
Order By: Relevance
“…For lung cancer, the ERR/Gy increases with smoking up to approximately 10 cigarettes per day and then decreases, approaching no radiation-associated excess risk for subjects who smoke 20 or more cigarettes per day, a similar pattern was found in previously reported work (1, 2, 8). In the moderate smoking intensity range near 10 cigarettes per day, smoking could promote radiation-initiated cells by causing inflammation in the tissue microenvironment (9).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…For lung cancer, the ERR/Gy increases with smoking up to approximately 10 cigarettes per day and then decreases, approaching no radiation-associated excess risk for subjects who smoke 20 or more cigarettes per day, a similar pattern was found in previously reported work (1, 2, 8). In the moderate smoking intensity range near 10 cigarettes per day, smoking could promote radiation-initiated cells by causing inflammation in the tissue microenvironment (9).…”
Section: Discussionsupporting
confidence: 86%
“…However, a sensitivity analyses, which discounted smoking duration over the period of follow-up when smoking was unknown, suggests that the radiation effect and smoking-radiation effect modification were not particularly sensitive to the incompleteness of the smoking history data. In the current analysis, we considered all lung cancer types together, while smoking and radiation have different effects on different subtypes of lung cancer (2). However, it should be noted that the nature of the joint effects of smoking and radiation showed a similar pattern for different types of lung cancer (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADR is also inducible in spermatogonial cells of mice, but it is not transmitted to offspring [131]. In A-bomb survivors, radiation exposure influences the risk of lung cancer associated with tobacco smoking, including post-bombing smoking history, where the joint effects are less than additive; in this way it has been reported that radiation exposure tends to decrease the risk of smoking-associated lung cancer more efficiently in heavier smokers [133135]. A more pronounced effect of radiation exposure on heavier smokers is likely because the repair mechanism depends on the types and amount of damage in the genome.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern of radiation-related risks for solid cancer exhibits a gradual increase starting several years after the bombings, while the risk of leukemia increased in the early period immediately subsequent to the bombing, and then decreased (4,5). Although the clinicopathological features of several types of cancer have been investigated in these survivors (6)(7)(8), there are only a small number of studies on the clinicopathological features of urological cancer. To the best of our knowledge, there has been no report about the features of prostate cancer (PCa) in A-bomb survivors.…”
Section: Introductionmentioning
confidence: 99%